Rare case of disseminated mucormycosis presenting with bilateral pulmonary artery aneurysm - Vikas Marwah; Saurabh Tiwari; S P S. Shergill; P S Mishra; Saikat Bhattacharjee (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2021)
Pulmonary artery aneurysm is an infrequent entity and is generally congenital in origin or secondary to pulmonary arterial hypertension. Infections causing pulmonary artery aneurysm are limited, in which tuberculosis and bacterial infections being the shared causative etiologies. There have been only scarce cases reported in the past, in which mucor caused pulmonary artery aneurysm. Pulmonary mucormycosis causing pulmonary artery aneurysm is an infrequent and almost fatal complication, as most of the diagnoses are made postmortem. Our case is the first case report in Indian literature that brings out a case of disseminated mucormycosis, causing bilateral segmental pulmonary artery aneurysm in a patient with uncontrolled diabetes. This patient was cured by timely treatment with antifungals.